Error estimation of the integral tau method for fourth order overdetermined ODES - Victoria O. Ojo; Emmanuel O. Adeyefa; Ezekiel O. Faniyi; Rotimi O. Folaranmi (ZBW - Leibniz Information Centre for Economics, 2023)
This paper presents the error estimate for the integrated formulation of the tau method for over-determined ordinary differential equations. In the earlier works of these authors, the generalized error estimation of tau approximates for the ODES for the integrated formulation for non-overdetermined ODES was reported. In this work emphasis is laid on the error and error estimate, we established the accuracy of the results using the principle of mathematical induction and through some numerical experiments.
Keywords: 330; Ordinary Differential equation; Variance; Formulation; Error Estimation